Effect of sorghum varieties on the quality of Xiaoqu light-flavor Baijiu - LAI Yucheng, ZHANG Ying, LI Xiumei, ZHE Hongbin, PU Weiying, XIE Lianfen, HE Mengchao, SUN Zhiwei, ZHAO Jinsong, HAN Xinglin (Zhongguo niangzao)
In order to explore the effect of sorghum varieties on the quality of Xiaoqu light-flavor (Qingxiangxing) Baijiu, the physical and chemical indexes of red and white sorghum and the total acids, total esters, volatile flavor components and organic acids of the brewed Xiaoqu light-flavor Baijiu base liquor samples were analyzed. The Xiaoqu light-flavor Baijiu samples were numbered YLQ1 (red sorghum), YLQ2 (white sorghum) and YLQ3 (red and white sorghum mass ratio 1∶1), respectively. The characteristic volatile compounds were screened by odor activity value (OAV), and the sensory evaluation of Xiaoqu light-flavor Baijiu was performed. The results showed that the tannin content of the sample YLQ1 was higher (1.16 g/100 g), but the protein, crude fat and starch contents were not significantly different (P<0.05). The contents of total acid and total ester in the sample YLQ2 were the highest (1.16 g/L and 1.17 g/L, respectively). A total of 32 flavor substances were detected in the 3 kinds of Xiaoqu light-flavor Baijiu, including 10 alcohols, 6 aldehydes, 5 acids, 9 esters, and 1 aromatic compound and 1 pyrazine compound each. With OAV>1 as the index, 18 kinds of characteristic flavor compounds were selected. Among them, 2,3-butanediol (L-racemic), acetaldehyde, acetal, isoamyl acetate, ethyl valerate and ethyl caproate had obvious contribution to the flavor of 3 kinds of Xiaoqu light-flavor Baijiu. Combined with sensory evaluation, the bitterness, pungency and other miscellaneous taste of the sample YLQ2 brewed from glutinous white sorghum single grain were lower, and the body softness, harmony and overall style were better.